Determination of Anxiety Levels and Knowledge Levels about COVID-19 during COVID-19 Outbreak of Pregnants: Survey in Turkey - Yüksekol, Özlem Doğan; Nazik, Feyza; Baltacı, Nazlı; Ulucan, Mihriban (Dokuz Eylül Üniversitesi, 2023)
Purpose: To determine the fears and level of knowledge of pregnant women about outbreaks during the COVID 19 outbreak. Methods: This was conducted as descriptive research with 276 pregnant women admitted to women's health and maternity outpatient clinic of hospitals in eastern Turkey. The data was collected using the personal information form, the information levels form for COVID-19, and the COVID-19 Anxiety Scale. Results: It was found that 75.4% of pregnant women were worried that they would catch coronavirus in the hospital during or after childbirth. The average score of women on the COVID-19 Anxiety Scale was 6.7±2.4 (min:5, max:14). The anxiety level of the pregnant women who were in the last trimester of pregnancy, who did not receive information about COVID-19, who changed their delivery method due to the pandemic, who received inadequate prenatal care, whose social support decreased, and who felt vulnerable, were significantly higher. Conclusions: The research revealed that anxiety in pregnant women is affected by some factors. It is important to provide care and support for these groups.
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi